Knowledge, beliefs and practices towards HIV/AIDS among adolescents in India: A scoping review protocol. - Pranita Patsani; Jayashree Parida; Arpita Panda; Susangita Jena; Swati Sukalyani Behera; Abinash Pradhan; Prasanna Kumar Patra; Sanghamitra Pati; Harpreet Kaur; Subhendu Kumar Acharya (PLoS ONE)
Introduction Acquired Immune Deficiency Syndrome (AIDS) is a major health concern among Indian adolescents (10-19 years). Indian adolescents lack adequate knowledge about HIV/AIDS and adopt wrong practices. The present scoping review aims to understand the status of knowledge, beliefs and practices among Indian adolescents about HIV or HIV/AIDS. The present study will also focus on their understanding and the source of knowledge and awareness regarding HIV/AIDS. Methodology The recommendations of Arksey and O'Malley in 2005, Levac et al. in 2010 and The Joanna Briggs Institute Reviewers' manual in 2015 to conduct a systematic scoping review will be employed. The review questions, eligibility criteria and search strategy for this study will be ensured by the Population, Concept and Context (PCC) strategy. The Preferred Reporting Items for Systemic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) will be used for reporting of this scoping review. The methodological quality of all the relevant studies will be assessed by the Mixed Methods Appraisal Tool (MMAT), Version- 2018. Literature search will be carried out by using electronic databases such as PubMed, APA PsycInfo, EMBASE, and Google Scholar. Cross-references will be used to extract additional studies. Ethics and dissemination As the planned study is based on secondary data and doesn't involve human and animal subjects, there is no requirement for formal ethical approval. Strengths and limitations of the study The planned scoping review is the first of such study on the topic of HIV/AIDS among adolescent population in India as per the electronically available literature.There will be quality assessment of all the included studies.A thorough search strategy will be conducted as per the recommendations of the experts in scoping review search.On limitation side, the planned study will only utilize electronically available resources/evidences that are written in English language.The planned evidence based study will be of much help for the healthcare professionals and policy makers.